2014
DOI: 10.1002/jbm.a.35390
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of ferroelectric lithium niobate and the influence of polarization charge on osteoblast proliferation and function

Abstract: In this work, the influence of substrate surface charge on in vitro osteoblast cell proliferation on ferroelectric lithium niobate (LN) crystal surfaces is investigated. LN has a spontaneous polarization along the z-axis and is thus characterized by positive and negative bound polarization charge at the +z and -z surfaces. Biocompatibility of LN was demonstrated via culturing and fluorescence imaging of MC3T3 osteoblast cells for up to 11 days. The cells showed enhanced proliferation rates and improved osteobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 64 publications
4
51
0
Order By: Relevance
“…The proliferation rate looks similar on the faces of LN and slightly higher than that on glass in the first 24 h, while negligible differences are observed after 48 h for all of the substrates. In fact, the population increases by ∼90% on LN faces and by ∼40% on glass, showing around 50% faster proliferation on LN, compared to glass in the first 24 h. This is in good agreement with the results reported by Carville et al, 31 who found significant differences in osteoblast cell proliferation between c+ and c− were observed after incubation for only 6 days.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…The proliferation rate looks similar on the faces of LN and slightly higher than that on glass in the first 24 h, while negligible differences are observed after 48 h for all of the substrates. In fact, the population increases by ∼90% on LN faces and by ∼40% on glass, showing around 50% faster proliferation on LN, compared to glass in the first 24 h. This is in good agreement with the results reported by Carville et al, 31 who found significant differences in osteoblast cell proliferation between c+ and c− were observed after incubation for only 6 days.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…19) and PPLT. 29 The results point to promising research directions exploiting LiNbO 3 as a neural substrate.…”
Section: à2mentioning
confidence: 99%
“…Alternatively, topographical features can be created in monodomain substrates via photo-or electron beam lithography. Recent work showed that uncoated LiNbO 3 surfaces are biocompatible with celltype specific effects: osteoblasts 19 and mesenchymal stem cells 20 exhibited increased proliferation and differentiation on charged Published by AIP Publishing. 110, 053702-1 charge was also shown to affect cell morphology and motility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ferroelectric properties of certain crystals such as Lithium Niobate have been exploited recently to investigate the role of charge on cell behavior, and show great promise. 52 Ferroelectric materials have a spontaneous polarization which can be switched by an externally applied electric field. Therefore modulating polarization domains of user-specified size and shape are possible and this combined with the possibility of optically transparent samples yields a substrate ideal for cell-charge experiments.…”
Section: Effect Of Substrate Stiffnessmentioning
confidence: 99%